A transcriptional evaluation of the melanoma and squamous cell carcinoma TIL compartment reveals an unexpected spectrum of exhausted and functional T cells - Cameron, Cheryl M.; Richardson, Brian; Golden, Jackelyn B.; Phoon, Yee Peng; Tamilselvan, Banumathi; Pfannenstiel, Lukas; Thapaliya, Samjhana; Roversi, Gustavo; Gao, Xing-Huang; Zagore, Leah L.; Cameron, Mark J.; Gastman, Brian R. (Frontiers in Oncology, 2023)
Significant heterogeneity exists within the tumor infiltrating CD8 T cell population, and exhausted T cells harbor a subpopulation that may be replicating and retain signatures of activation, with potential functional consequences in tumor progression. Dysfunctional immunity in the tumor microenvironment is associated with poor cancer outcomes, making exploration of these exhausted T cell subpopulations critical to the improvement of therapeutic approaches. To investigate mechanisms associated with terminally exhausted T cells, we sorted and performed transcriptional profiling of CD8+ tumor infiltrating lymphocytes (TIL) coexpressing the exhaustion markers PD-1 and TIM-3, from large volume melanoma tumors. We additionally performed immunologic phenotyping and functional validation, including at the single cell level, to identify potential mechanisms that underlie their dysfunctional phenotype. We identified novel dysregulated pathways in CD8+PD-1+TIM-3+ cells that have not been well studied in TIL; these include bile acid and peroxisome pathway-related metabolism, and mammalian target of rapamycin (mTOR) signaling pathways, which are highly correlated with immune checkpoint receptor expression. Through bioinformatic integration of immunophenotypic data and network analysis, we propose unexpected targets for therapies to rescue the immune response to tumors in melanoma.